Ageing masculinities in Irish literature and visual culture
1 online resource (xiv, 252 pages)
Keywords: "This book engages with ageing masculinities in Irish literature and visual culture, including fiction, drama, poetry, painting, and documentary. Exploring the shifting representations of older men from the early twentieth century to the present, the contributors analyse how a broad range of literary and visual texts construct, reinscribe, or challenge perceptions of older age. In doing so, they trace a shift from depictions of authority figures - often symbolising patriarchal dominance and oppression - to more nuanced, complex, and heterogeneous explorations of older men's embodied subjectivities and vulnerabilities. Exploring artists and writers such as Seán Keating, J.M. Synge, Teresa Deevy, Marina Carr, Seamus Heaney, Paul Muldoon, Derek Mahon, Kate O'Brien, John Banville, Colm Tóibín, Bernard MacLaverty, Mike McCormack, Anne Griffin, and Claire Keegan, the essays in this collection attend to the symbolic as well as social significance of older men in Irish cultural expression"--